Concurrent comparison of epidemiology, clinical presentation and outcome between adult patients suffering from the pandemic influenza A (H1N1) 2009 virus and the seasonal influenza A virus infection. Issue 1019 (5th August 2010) - To, Kelvin K W; Wong, Samson S Y; Li, Iris W S; Hung, Ivan F N; Tse, Herman; Woo, Patrick C Y; Chan, Kwok-Hung; Yuen, Kwok-Yung
Abstract : Purpose of study: The demographics, clinical features and outcome of patients with pandemic influenza A (H1N1) 2009 infection were compared with a concurrent cohort of patients with seasonal influenza A infection. Study design: The clinical and microbiological data of hospitalised adult patients admitted between 29 June and 28 October 2009, with pandemic A (H1N1) 2009 or seasonal influenza A infection, were analysed. Results: A total of 186 patients including 69 pandemic A (H1N1) and 117 seasonal influenza were analysed. The majority (75%) under 50 years of age had pandemic A (H1N1). Compared with seasonal influenza, pandemic A (H1N1) patients were younger (median age 47 years vs 76 years, p<0.001), less likely to have lower respiratory tract symptoms (46.4% vs 66.7%, p=0.007), but more likely to be obese (5.8% vs 0%, p=0.018), pregnant (7.2% vs 0.9%, p=0.027) or have no underlying predisposing factors (24.6% vs 5.1%, p<0.001). Patients with pandemic A (H1N1) were more likely to receive oseltamivir (91.3% vs 40.2%, p<0.001), but less likely to receive antibiotics (75.4% vs 90.6%, p=0.005). Respiratory failure was the reason for intensive care unit admission for all four patients with pandemic A (H1N1), but only for one of three patients with seasonal influenza. There were no statistical significant differences in the rate of intensive care unit admission or death. Conclusions: In addition to age, several clinical parameters were different between pandemic A (H1N1) and seasonal influenza. However, since both seasonal and pandemic influenza can lead to significant morbidity and mortality, the impact of pre-existing seasonal influenza should not be underestimated during the pandemic period.